Environmental movements in a material world. A relational perspective on single-use plastic in Penzance, UK - Idies, Yusif; Mössner, Samuel (Frontiers in Sustainable Cities, 2023)
In the discursive battle about the big and important ideas, some topics are considered more important than others and more likely to mobilize society. More recently, marine plastic pollution has become a key topic for environmental movements. In this study, we aimed to contribute to a more detailed understanding of how specific issues of sustainability are brought forth. Conceptually, we argue that recourse to relational theories from science and technology studies might help to strengthen the conceptualization of social movement research. By drawing on the concept of “boundary objects”, we extend the range of social movement approaches in order to better understand how the process of framing is put to work materially. The focus on boundary objects can therefore explain the selective formation of environmental discourses and policies when applied to the field of environmental protection and sustainability.